2001
DOI: 10.1016/s0022-2275(20)31511-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dietary fatty acid composition on the relationship between CETP activity and plasma lipoproteins in monkeys

Abstract: CETP activity, measured as transfer of cholesteryl ester from exogenous HDL to exogenous VLDL and LDL, reflecting CETP mass as determined by ELISA, was documented in three groups of St. Kitts vervet monkeys fed diets enriched in saturated (Sat), monounsaturated (Mono), or n-6 polyunsaturated (Poly) fatty acids. CETP activity was not different when comparing the three dietary fats. However, CETP activity was significantly higher when cholesterol was added to each of the diets. Significant positive associations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Thus, while these two studies were both conducted in patients with T2D, there is a wide variation in frequency of the ‘B1B1’ genotype between the two studies and this affects the interpretation of the findings. In an animal study performed in feral adult male St. Kitts vervet monkeys ( Cercopithecus aethiops sabeus ) [ 44 ], SFA was shown to increase CETP activity, thereby reducing HDL levels which might explain the findings of the study in the American population [ 13 ]. However, in the animal study [ 44 ], the effect of SFA on CETP activity was only observed when cholesterol was added to the diet.…”
Section: Results Of Database Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, while these two studies were both conducted in patients with T2D, there is a wide variation in frequency of the ‘B1B1’ genotype between the two studies and this affects the interpretation of the findings. In an animal study performed in feral adult male St. Kitts vervet monkeys ( Cercopithecus aethiops sabeus ) [ 44 ], SFA was shown to increase CETP activity, thereby reducing HDL levels which might explain the findings of the study in the American population [ 13 ]. However, in the animal study [ 44 ], the effect of SFA on CETP activity was only observed when cholesterol was added to the diet.…”
Section: Results Of Database Searchmentioning
confidence: 99%
“…In an animal study performed in feral adult male St. Kitts vervet monkeys ( Cercopithecus aethiops sabeus ) [ 44 ], SFA was shown to increase CETP activity, thereby reducing HDL levels which might explain the findings of the study in the American population [ 13 ]. However, in the animal study [ 44 ], the effect of SFA on CETP activity was only observed when cholesterol was added to the diet. SFA has also been shown to lower the number of LDL receptors in the liver, which slows the removal of apolipoprotein B (ApoB)–containing lipoproteins [ 45 ], with the resulting effect of a decrease in HDL levels.…”
Section: Results Of Database Searchmentioning
confidence: 99%
“…CETP activity could be affected by both gene 50 and environmental factors such as diet, 51 especially in people with T2DM. Based on our knowledge, the present study investigates, for the first time, the interaction between diet quality indices, including; HEI, DQI and DPI and CETP Taq1B polymorphism.…”
Section: Introductionmentioning
confidence: 99%
“…26 In this study, the vervet monkey model was utilized because of the similarities that appear to exist with humans in terms of the intravascular metabolism of cholesterol which are further enhanced by having an active cholesteryl ester transfer system. 27 Therefore, 16 vervet monkeys were utilized to investigate the possible presence of PCSK9 polymorphisms and their impact on CVDs.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the current study was aimed at acquiring PCSK9 mutations that underscore heritable variations of lipoproteins, as opposed to replicating the exact genetic variants that are found in humans 26 . In this study, the vervet monkey model was utilized because of the similarities that appear to exist with humans in terms of the intravascular metabolism of cholesterol which are further enhanced by having an active cholesteryl ester transfer system 27 . Therefore, 16 vervet monkeys were utilized to investigate the possible presence of PCSK9 polymorphisms and their impact on CVDs.…”
Section: Introductionmentioning
confidence: 99%